1985
DOI: 10.1210/endo-117-6-2553
|View full text |Cite
|
Sign up to set email alerts
|

Production of Insulin-Like Growth Factors by Ovarian Granulosa Cells

Abstract: Evidence for ovarian secretion of somatomedins or insulin-like growth factors (IGF's) was generated by two approaches. First, porcine granulosa cells were shown to produce IGF's and an IGF-binding protein under serum-free conditions in vitro. The ovarian IGF's were recognized in two competitive binding assays specific for IGF's, a RIA using antibodies to human IGF-I and a radioreceptor assay using rat liver plasma membranes. IGF secretion was maintained for at least 10 days in culture. Second, ovarian producti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
67
3
2

Year Published

1986
1986
2002
2002

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 220 publications
(76 citation statements)
references
References 0 publications
4
67
3
2
Order By: Relevance
“…In addition to this, in a series of in-vitro studies, Adashi and his colleagues (1985a) found that incubation of granulosa cells with insulin and insulin-like growth factor-I (IGF-I) augmented their responses to stimulation by FSH. These studies have been confirmed and extended by others (Hammond et al, 1985;Davoren & Hsueh, 1986;Jia et al, 1986). Following the hypothesis that G H or IGF-I can facilitate granulosa cell responsiveness to gonadotrophins, a series of studies demonstrated that co-treatment with G H augmented the ovarian response to stimulation by gonadotrophins (Homburg et al.…”
mentioning
confidence: 69%
“…In addition to this, in a series of in-vitro studies, Adashi and his colleagues (1985a) found that incubation of granulosa cells with insulin and insulin-like growth factor-I (IGF-I) augmented their responses to stimulation by FSH. These studies have been confirmed and extended by others (Hammond et al, 1985;Davoren & Hsueh, 1986;Jia et al, 1986). Following the hypothesis that G H or IGF-I can facilitate granulosa cell responsiveness to gonadotrophins, a series of studies demonstrated that co-treatment with G H augmented the ovarian response to stimulation by gonadotrophins (Homburg et al.…”
mentioning
confidence: 69%
“…IGF-I mRNA is also expressed in CL, and its highest expression was observed during the early, mid and late luteal phases [77]. During follicular growth both IGF-I and II concentrations increase in follicular fluid [37], and are also increased in follicular fluid by gonadotropins [38] and GH [14].…”
Section: Endocrine Effects Of Igf-i On Reproductive Functionmentioning
confidence: 99%
“…In both rat (Borland etal., 1984 ;Mita etal., 1985 ;Oonk etal., 1987a, b) and pig (Jaillard et al, 1987, present (Hammond et al, 1985;Hsu and Hammond, 1987) and rat (Davoren and Hsueh, 1986) granulosa cells and their purtative male homolog, Sertoli cells from the same species (Ritzen, 1983 ;Tres et al, 1986 ;Smith et al, 1987 ;IChatelain etal., 1987), secrete Sm-C/IGF-I immunoreactivity in the medium. The Sm-C/IGF-I-like peptide purified from rat (Smith etal., 1987) The physiological in vivo significance of the endocrine/paracrine/autocrine role of Sm-C/IGF-I on testicular growth and functions is suggested by the fact that in both humans (Tanner et al, 1975 ;Kulin et al, 1981 ;Laron, 1984) Les LC contiennent des récepteurs spécifiques pour la Sm-C/IGF-1 et pour l'insuline, tandis que les SC contiennent seulement des récepteurs pour la Sm-C/IGF-1.…”
mentioning
confidence: 99%